INSTITUTIONAL ANALYSIS OF FOOD SECURITY IN SABAH - Firdausi Suffian; Ika Suzieana Jamluddin; Faridah Suffian (Journal of Islamic, Social, Economics and Development, 2022)
The key concern over food security boils down to the role of institutions to prioritize the agenda in agriculture policy. The role of institutions plays primary role to orchestrate food policy agenda, coordinate and implement agro-food policy so that food sector can contribute at least sufficient supply with less dependent on food import. The pandemic-induced crisis has manifested the importance of food security across the globe. Lockdown and trade restriction have disrupted the food production supply chain and raised the concern over accessibility of food supply. The threats of food security are policymaker paying less attention on the importance of food sector rather focus on the lucrative industrial crops sectors. Worst still, industrial crops sector only focusses on extractive activities and limited downstream to support the local agro-food and sub-sectors. This research explores food security issues in Sabah which is one of the rich resource states in Malaysia. Agriculture sector contributes significantly to the state economy and mostly dominated by industrial crops. The over dominance of industrial crops activities made the state dependent on food import which constituted the largest import of the state. Though industrial crops are one of the important export gains for the state but depending on food import may lead to higher food prices, which will push governments to impose price ceilings, further stressing supply capacity. This will hurt the population and most vulnerable ones. So, this research intended to understand food security issues and constraining factors for expanding agro-food production